Tackling The Issue Of Credibility In Phenomenographic Interviewing To Capture Problem-based Learning (PBL) Experience - Suraini Mohd-Ali,; Fariza Puteh-Behak,; Noor Saazai Md Saat,; Ramiaida Darmi,; Haliza Harun; Rosni Samah (MCSER-Mediterranean Center of Social and Education, 2024)
The trustworthiness of any qualitative research is frequently questioned by positivists, perhaps because their notions of validity and reliability cannot be addressed in the same way in naturalistic work although, the framework for trustworthiness in this form of work have been in existence for many years. There are four issues of trustworthiness that are central in any qualitative research paradigm namely credibility, transferability, dependability, and confirmability (Lincoln & Guba, 1985). In this paper, the focus is on credibility issue in phenomenographic interviewing. Credibility is present when the research results mirror the view of the participants understudy. Investigating conceptions is the aim of phenomenographic researches and interview is commonly used as a tool to access people’s conceptions. The goal in phenomenographic research is to study the phenomenon through the lens of the participants hence, there is a high reliance on the data from the interviews with the research participants. In light of that, the phenomenographic researchers will have to exercise caution in carrying out the interviews to ensure the credibility of the data, which reflects the voice of the participants, is taken care of. Using the data from one of the author’s current research on learners’ experiences in Problem-Based Learning (PBL), the author illustrates the kind of interview questions or prompts used to elicit responses and how the credibility of the data (content-related credibility, credibility of method and communicative credibility) was attained by employing five interviewing strategies: 1) begin with superficially shared topic, 2) follow up questions focusing on eliciting ideas/concepts, 3) more follow up questions to get concrete examples of the ideas/concepts, 4) the use of empathy in the interview and 5) bracketing interviewer’s assumptions.